Unravelling conceptualizations of (in)equality in early childhood education and care system. Issue 1 (2nd January 2019) - Paananen, Maiju; Repo, Katja; Eerola, Petteri; Alasuutari, Maarit
ABSTRACT: Early childhood education's role in increasing equality in society has been highlighted by international organizations. However, it is unclear what is meant by the concept of equality in different situations, as the meaning fluctuates and reflects the cultural political contexts in which it is embedded. In this paper, we analyse the equality discourses of local early childhood education and care (ECEC) policymakers in Finland, drawing on different conceptualizations of equality and social justice. In doing so, we show that the way in which equality is conceptualized differs – along with the suggested remedies – depending on whether the subjects of equality are adults, children at the border of an institutional setting, or children within the ECEC institution.